Além da geração de trabalho e renda: economia solidária e participação de cooperados/associados em Sergipe - Vasconcelos, Maria da Conceição Almeida (2007)
This thesis has as study object the solidary economy. It is its intention to analyze the solidary economy, while a possibility to generate work and income and of exercise of the participation, being had themselves as reference previous the personal and work experiences of cooperated/the associates, the experiences of the collective work in the solidary economical enterprises, including also the formation continued. One is about a research developed in three located solidary economical enterprises in the State of Sergipe, with activities in the branches of solid residues, confection and improvement of the shrimp. In the research, the qualitative method was used, understanding the collection of depositions gotten by means of half-structuralized interviews, participant and research bibliographical and documentary comment. Moreover, they had been used given statisticians for the characterization of the enterprises and it s cooperated/associates. The theoretical landmark has as base authors who study thematic of the solidary economy and the participation. The results had disclosed that the searched enterprises come propitiating the generation of work and income for cooperated/the associates, even so still are limited the financial results. However, the experiences show that the insertion in the enterprises, goes beyond the generation of work and income. Such experiences are bringing significant changes for the cooperated lives of/the associates, being distinguished: the learning of the automanagement collective work; the personal growth; the discovery and the development of potentialities; the magnifying of the vision of world and the importance of the participation in other social instances. It has, still, a long way to cover, as much in the direction of the consolidation of the enterprises and an effective generation of income as in the perspective of the automanagement and construction of a solidary and participative culture that assures the effective exercise of the citizenship